Impact of gear choice on open access fisheries: A study on fishery regimes - Santiago Gomez; Johannes Kammerer (University of Heidelberg, Department of Economics, 2023)
The regulation of gears constitutes a fisheries management strategy primarily aimed at preserving immature fish. This approach circumvents the politically sensitive and difficult-to-enforce direct restrictions on entry and catches that characterize many developing contexts. However, existing recommendations often oversimplify socioeconomic dimensions and assume complete government control over gear selection. This oversimplification overlooks crucial effects resulting from the fishers' agency. To address this gap, our study highlights the implications of fishing gear selection in the outcomes of a fishery. We propose that the choice of fishing gear, i.e., the ability of fishers to select for different fish sizes, has significant direct implications for management due to the distinct fishery regimes it leads to. A swift transition between two states characterizes these regimes: one with high output value and a significant proportion of fishers targeting large fish, and the other with low output value and a predominant number of fishers aiming for small fish. These regimes emerge in response to contextual variables such as prices and economic activity and are not a product of government intervention. Policy management operates on top of these regimes, taking advantage of or hampered by them depending on the context. Our findings are derived from an agent-based model replicating the general conditions on the Nile Perch Fishery in Lake Victoria and accurately simulating its age-structured fish stock. This allows for dynamic shifts driven by gear choices that target different fish sizes.
urn:nbn:de:bsz:16-heidok-337728
Keywords: 330; Gear Selectivity; Gear Choice; Agent Based Modeling; Nile Perch Fishery; Lake Victoria